Antiepileptic drug compliance among caregivers of children with epilepsy: An observational cohort study - Aulakh, Roosy (Indian Journal of Child Health, 2018)
Background: Poor compliance with antiepileptic drugs (AEDs) not only increases morbidity and mortality rates among the children with epilepsy but it also leads to multiple hospital emergency room visits and enhanced health-care costs. Objective: The objective of the study was to delineate the prevalence and causes of antiepileptic drug non-compliance among caregivers of children with epilepsy in a tertiary care hospital in North India. Materials and Methods: Basic demographic data along with details of AED compliance (method of dispensing, exact dose being dispensed, frequency of administration, missing out on doses, and any side effects noted) were taken from primary caretaker dispensing the medication to the enrolled children with epilepsy on monotherapy with AEDs. Results: Wrong dosage of AED dispensed was reported in 20% (overdosing reported in 8% and underdosing in 12%) of the enrolled children. One child among the study participants receiving an overdose of the prescribed AED had emergency room admission with phenytoin toxicity. One child among the study participants was receiving wrong AED while another was receiving the AED in wrong frequency. Conclusions: The results from the present study highlight the high level of antiepileptic drug noncompliance among caregivers of children with epilepsy and also the various reasons leading to the wrong administration of AEDs to children with epilepsy. These ground level issues related to poor AED compliance, among caregivers of children with epilepsy, can help devise various methods to address these so as to improve the compliance to AEDs by caregivers of children with epilepsy.